Conformity of Labeling into Real Composition of Local and Imported Chicken Burgers Sold in the State of Kuwait - Al-Bahouh, Mariam E.; Al-Zenki, Sameer F.; Alomirah, Husam; Al-Failee, Betool; Al-Mutairi, Tahani; Khan, Abdul-Rehman (International Journal of Poultry Science, 2012)
Food authenticity is considered to be one of the most important issues that affect food quality. Food authenticity is very crucial for a country like the State of Kuwait which imports more than 90% of its processed food from countries where the processing conditions are unknown. Chicken burger has been considered as a model food for this study. Thus, the purpose of this study is to evaluate the proximate analysis, added water and hydroxyproline contents, in addition to determine any false description on the label, or substitutions of cheaper ingredients which make the chicken burgers fall short in meeting meat quality standards. Chicken burgers (local and imported) analyzed in this study were purchased from different co-operatives, fast food restaurants and retail suppliers. Proximate analysis revealed a wide variation in the composition and nutritive value among samples. Most of the local chicken burgers had higher protein (p0.05) and moisture content (p>0.05) and lower fat (p0.05) than those imported. Furthermore, both local and imported chicken burgers had high percentage of added water (p0.05), with respect to the standard, which give clear indication of fraudulence, as these ingredients are used to increase the size and weight of the final products without any regard to the nutritional value. Therefore, the results of the present study emphases the importance of conducting such studies to monitor and compare the quality of local and imported food products in the State of Kuwait.